Dynamics in the compositions of the string quartet among Iraqi musicians (Journal of the College of Basic Education, 2023)
Musical authors, since the eighteenth century until the present, have paid increasing attention to defining the methods of performing musical tones in musical works, hence the need to invent technical terms and expression terms specific to the nature of musical performance, which I added A beautiful and honest expression that easily reaches the minds of listeners of musical compositions, expressing the feelings of the author or the interests of his community, as well as the conductor and the orchestra in general.Musical dynamism is one of the most prominent expressive means in musical performance, which is closely related to the level of evaluation of musical compositions and their good performance or not, by specialized musicians, which results in sympathy or acceptance at least as a reaction to the recipient. The study of dynamics is linked to many controls (which will be mentioned), foremost of which is the ability of the composer to correctly use the elements of musical expression stemming from their importance and real function for him. From here, I found the need to study dynamics to help evaluate the different musical works as well as approximating the description of the true feelings of the author. Here, the researcher asks, does the dynamic have an importance and a function for Iraqi composers, including Abdul Razzaq Al-Azzawi?